2010
DOI: 10.1371/journal.pgen.1001087
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of GSK-3 Ameliorates Aβ Pathology in an Adult-Onset Drosophila Model of Alzheimer's Disease

Abstract: Aβ peptide accumulation is thought to be the primary event in the pathogenesis of Alzheimer's disease (AD), with downstream neurotoxic effects including the hyperphosphorylation of tau protein. Glycogen synthase kinase-3 (GSK-3) is increasingly implicated as playing a pivotal role in this amyloid cascade. We have developed an adult-onset Drosophila model of AD, using an inducible gene expression system to express Arctic mutant Aβ42 specifically in adult neurons, to avoid developmental effects. Aβ42 accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
154
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(166 citation statements)
references
References 81 publications
(119 reference statements)
12
154
0
Order By: Relevance
“…Although this effect of lithium in vitro was mimicked by transfection with siRNA of GSK-3a but not GSK-3b , other in vitro and in vivo studies found that GSK-3b inhibition also mimicked the ability of lithium or VPA to suppress the process of Ab formation from APP (Su et al, 2002(Su et al, , 2004Qing et al, 2008). A recent study in an adultonset Drosophila model of AD demonstrated a novel mechanism, whereby GSK-3 directly regulated Ab42 levels in the absence of any effects on APP processing (Sofola et al, 2010).…”
Section: Admentioning
confidence: 99%
“…Although this effect of lithium in vitro was mimicked by transfection with siRNA of GSK-3a but not GSK-3b , other in vitro and in vivo studies found that GSK-3b inhibition also mimicked the ability of lithium or VPA to suppress the process of Ab formation from APP (Su et al, 2002(Su et al, , 2004Qing et al, 2008). A recent study in an adultonset Drosophila model of AD demonstrated a novel mechanism, whereby GSK-3 directly regulated Ab42 levels in the absence of any effects on APP processing (Sofola et al, 2010).…”
Section: Admentioning
confidence: 99%
“…28,29,30 In A -overexpressing transgenic models for AD, lithium treatment consistently decreases A levels, GSK-3 activity and tau phosphorylation. 29,31,32,33,34 In such models, lithium is reported to prevent A toxicity, 32 preserve dendritic structure, 31 promote neurogenesis 34 and rescue A -induced cognitive impairment. 31,33,34 Similarly, in transgenic mice that overexpress pathogenic mutant tau, lithium treatment reduced levels of hyperphosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Drosophila models for Alzheimer's disease were developed (Finelli et al, 2004;Greeve et al, 2004;Crowther et al, 2005), and several factors (such as insulindegrading enzyme, apolipoprotein E, oxidative stress) known to be related to Alzheimer's disease were studied with these Drosophila models (Rival et al, 2009;Sarantseva et al, 2009;Sofola et al, 2010;Tsuda et al, 2010;Ling and Salvaterra, 2011). Work from these groups has shown that Drosophila recapitulates several pathological features also seen in Alzheimer's disease.…”
mentioning
confidence: 99%